Pengaruh Konseling Kelompok Dengan Pendekatan Solution Focused Brief Counseling (SFBC) Terhadap Peningkatan Komunikasi Interpersonal Santri - Widayanti, Veni (Prosiding University Research Colloquium, 2021)
This study aims to examine the effect of group counseling with a solution focused brief counseling (SFBC) approach to improving students' interpersonal communication. In this study using the One Group Pretest and Posttest designs, the design used one group of subjects with one type of treatment, namely the experimental group. The population in this study were students of class 2 KMI, amounting to 15 students.The number of samples in this study were 8 students who had low or moderate pretest scores.Determination of sampling using purposive sampling technique, namely determination based on predetermined objectives or characteristics. The method of analysis in this study used a parametric paired sample t-test The results of this study indicate that group counseling with a solution focused brief counseling (SFBC) approach has an effect on improving students' interpersonal communication. This is evidenced by the results of the paired sample t-test with a probability sig. (2-tailed) 0.001 <0.05. And with the difference in the mean score ofquestionnaire 23.35% interpersonal communication from the results pretest and posttest. This proves that group counseling with a solution focused brief counseling (SFBC) approach can improve students' interpersonal communication.